Conflict Resolution and Peace Education Transformations across Disciplines (In Factis Pax: Journal of Peace Education and Social Justice, 2013)
Candice C. Carter (ed.) Conflict Resolution and Peace Education Transformations across Disciplines, New York: Palgrave Macmillan, 2010. ISBN: 978-0-230-62063-6. 237pp.